Solution of Wave Equation in Radial Form by VIM. (29th March 2012) - Aminikhah, Hossein
Abstract : An analytic approximation to the solution of wave equation is studied. Wave equation is in radial form with indicated initial and boundary conditions, by variational iteration method it has been used to derive this approximation and some examples are presented to show the simplicity and efficiency of the method.